2010
DOI: 10.1007/s00418-010-0732-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-dependent rearrangements of actin and nuclear myosin I in the nucleolus

Abstract: Nuclear actin and nuclear myosin I (NMI) are important players in transcription of ribosomal genes. Transcription of rDNA takes place in highly organized intranuclear compartment, the nucleolus. In this study, we characterized the localization of these two proteins within the nucleolus of HeLa cells with high structural resolution by means of electron microscopy and gold-immunolabeling. We demonstrate that both actin and NMI are localized in specific compartments within the nucleolus, and the distribution of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The results were in line with the dynamic behaviour of NMI and its role in rDNA transcription (Percipalle et al 2006;Philimonenko et al 2010), through concentration of NMI mainly in the dense Wbrillar component (DFC) of actively transcribing nucleoli and co-localization with nascent transcripts. However, the studies also revealed, due to the observation of an NMI fraction that did not associate with rDNA transcription, additional roles of NMI in other nucleolar processes (e.g.…”
Section: Moleculessupporting
confidence: 81%
See 1 more Smart Citation
“…The results were in line with the dynamic behaviour of NMI and its role in rDNA transcription (Percipalle et al 2006;Philimonenko et al 2010), through concentration of NMI mainly in the dense Wbrillar component (DFC) of actively transcribing nucleoli and co-localization with nascent transcripts. However, the studies also revealed, due to the observation of an NMI fraction that did not associate with rDNA transcription, additional roles of NMI in other nucleolar processes (e.g.…”
Section: Moleculessupporting
confidence: 81%
“…An ultrastructural analysis of the nucleolar spatial arrangement of actin and nuclear myosin I (NMI) was performed by Philimonenko et al (2010) to derive functional implications. The results were in line with the dynamic behaviour of NMI and its role in rDNA transcription (Percipalle et al 2006;Philimonenko et al 2010), through concentration of NMI mainly in the dense Wbrillar component (DFC) of actively transcribing nucleoli and co-localization with nascent transcripts.…”
Section: Moleculesmentioning
confidence: 99%
“…These reports strongly suggest that the functions of nuclear myosins differ from that of cytoplasmic myosins. Indeed, nuclear myosin I was found to mediate the transcription of ribosomal RNA genes through cooperation with nuclear actin [23,25]; whereas nuclear myosin (II) was reported to function as a transcription factor in colonic smooth muscle cells to regulate the protein-coding genes (such as ICAM-1) and its transcriptional activity is dependent on the phosphorylation status of MLC 20 [16]. In the present study, we provide evidence for the first time that MYL2 localizes in both cytoplasm and nucleus of cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in vesicle trafficking (Yokota et al, 1995) and transcription of ribosomal proteins (Philimonenko et al, 2010). The myosin heavy-chain protein subunit is saltresponsive and is directly influenced by the vacuolar Na + /H + antiporter that mediates transport of Na + and K + into the vacuole (Sottosanto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%